New Situations-New Demands in Our Educational System – Learning Foreign Languages - Kh.Yu. Olimov; D.S.Jalolova (Research Parks Publishing LLC, 2021)
The article examines the development of educational and informational competences of students in the Pedagogics reform and the formation of professional qualities of future educators